2023
DOI: 10.1101/2023.02.01.526568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Empirical Study on the Motivation of Helping Behavior in Rats

Abstract: Using rodent models to explore the motivation of helping behaviors has become a new trend in recent years. Empathy, the alleviation of personal distress, and desire for social contact have been considered motivations for rodents to engage in helping behaviors. We used 108 Sprague-Dawley rats as subjects and modified the two-chambered helping behavior experimental setup in Carvalheiro and colleagues' study to explore the main motivations of helping behavior in rodents through three experiments. The findings sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“… Ueno et al (2019) obtained similar results in mice for the incentive value of the restraint tool. In addition, many studies have also confirmed the important incentive value of social contact/interaction ( Calcagnetti and Schechter, 1992 ; Peartree et al, 2012 ; Kitchenham et al, 2019 ; Han et al, 2023 ).…”
Section: Why Help Others: Pursuing Social Contact or Other Rewardsmentioning
confidence: 92%
“… Ueno et al (2019) obtained similar results in mice for the incentive value of the restraint tool. In addition, many studies have also confirmed the important incentive value of social contact/interaction ( Calcagnetti and Schechter, 1992 ; Peartree et al, 2012 ; Kitchenham et al, 2019 ; Han et al, 2023 ).…”
Section: Why Help Others: Pursuing Social Contact or Other Rewardsmentioning
confidence: 92%
“…Communicated content contains the basic contributions of the products, some experiences of shopping for the customers. These actions may guide to the EWOM (Chai & Zheng, 2019). In the network environment, the amount of WOM information is huge and growing rapidly, which affects consumers' cognition and evaluation of products or services to a large extent.…”
Section: Introductionmentioning
confidence: 99%